2022
DOI: 10.3389/fimmu.2022.966158
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain ketoacids derived from cancer cells modulate macrophage polarization and metabolic reprogramming

Abstract: Macrophages are prominent immune cells in the tumor microenvironment that can be educated into pro-tumoral phenotype by tumor cells to favor tumor growth and metastasis. The mechanisms that mediate a mutualistic relationship between tumor cells and macrophages remain poorly characterized. Here, we have shown in vitro that different human and murine cancer cell lines release branched-chain α-ketoacids (BCKAs) into the extracellular milieu, which influence macrophage polarization in an monocarboxylate transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In our study, however, CM from MCF-7 cells, which contained higher BCKA levels than CM from MDA-MB-231 cells, did not enhance VEGF production, suggesting the possible relationship between this pro-tumoral factor and BCKA exposure to be indirect or non-linear. On the other hand, Stage II MCF N/H -TEM decreased the secretion of the inflammatory factor TNF-α, also reported by Cai et al upon incubation with CM from LC cells [58].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In our study, however, CM from MCF-7 cells, which contained higher BCKA levels than CM from MDA-MB-231 cells, did not enhance VEGF production, suggesting the possible relationship between this pro-tumoral factor and BCKA exposure to be indirect or non-linear. On the other hand, Stage II MCF N/H -TEM decreased the secretion of the inflammatory factor TNF-α, also reported by Cai et al upon incubation with CM from LC cells [58].…”
Section: Discussionsupporting
confidence: 73%
“…BCKA can be further catabolized through an essentially irreversible reaction catalyzed by branched-chain ketoacid dehydrogenase (BCKDH), ultimately forming acetyl-CoA and succinyl-CoA, which can enter the TCA cycle for energy production [55] and/or lipid synthesis [56], as well as affect epigenetic regulation [52]. On the other hand, incomplete BCKA degradation can lead to their extracellular release, as recently observed for different cancer cell types [57][58][59]. The present study newly shows that MCF-7 cells excrete significantly more BCKA (and HIB, an intermediary in the KIV degradation pathway) than MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further treated M0-, M1-, or M2-type macrophages with RF-7 and found that CD86 was upregulated in all types of RAW264.7 cells (Figure E and Figure S16). To investigate the global response of M2-TAM repolarization induced by RF-7 , we performed an untargeted MS-based proteomic analysis on M2-type RAW264.7 cells treated with RF-7 . , Overall, 6797 protein groups were quantified and 29 differentially expressed proteins were found when comparing RF-7 -treated cells to the untreated M2-type RAW264.7 cells (Figure F). Functional analysis indicated that the most enriched categories of RF-7 upregulated proteins included DNA-templated transcription, regulation of JNK cascade, and stress-activated MAPK cascade (Figure S17).…”
Section: Resultsmentioning
confidence: 99%
“…BMDMs were generated as previously described [ 53 ]. Briefly, bone marrow cells were obtained by flushing the femurs and tibias of wild-type (WT), Phgdh fl/fl or Phgdh fl/fl Cx3cr1 -Cre mice aged 6 to 8 weeks.…”
Section: Methodsmentioning
confidence: 99%